Scope of Wood Scanning Applications in India - A Review - Shibu, C; Arya, C; VaysagP, C.P.; AnooV, E V (Indian Forester, 2022)
This article describes the opportunities of major wood scanning technologies in the Indian forestry field. Researchers have developed various non-destructive technologies to better understand the inner properties of wood. In the wood industry, the correct identification of wood species and their physical (in furniture industries) and chemical (in paper and pulp industries) characteristics is critical for end-use applications. The measurements of wood properties (Elastic properties, Thermal properties, Electrical properties, Dielectric properties, and Ionization radiation properties) with the help of wood scanning technologies are used for locating and quantifying wood decay and knots in both standing trees and logs. These measurements have been employed in various perspectives on forestry applications. For instance, measurement of Modulus of Elasticity (MoE) is used to assess thinning effects and tree health assessments, and as a breeding criterion in tree improvement. This article aims to describe major wood scanning technologies that provide tomography of wood and the scope of wood scanning technologies, and their current status in the Indian forestry field. The major wood scanning technologies include Acoustic Tomography, Electrical Impedance Tomography, Magnetic Induction Tomography, Radiography Computed Tomography, and Microwave Tomography.